Una vita oltre la maschera: Panimmaginismo e immanenza - D’Amato, Pierluca (Philosophy Kitchen - Rivista di filosofia contemporanea, 2016)
As all philosophical concepts, also the concept of person constitutes itself referring to a particular problem. The analysis drafted by Marcel Mauss regarding the genesis of the aforementioned category permits to analyse the problematic nucleus to which such concept refers to, disclosing that it responds to the necessity of solving the ancient problem of the link between mind and body in a specific perspective. In this respect, bergsonian theory of images represents a solid attempt of passing not only the habitual solution of the problem represented by the concept of person, but also the problem itself whereto refers.